The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/elan.201400731
|View full text |Cite
|
Sign up to set email alerts
|

Detection of p53 Gene by Using Genomagnetic Assay Combined with Carbon Nanotube Modified Disposable Sensor Technology

Abstract: Electrochemical monitoring of DNA hybridization related to p53 gene sequence was investigated using genomagnetic assay combined with single walled carbon nanotube (SWCNT) modified pencil graphite electrodes (PGEs). The hybridization was performed either at magnetic beads (MB) surface or in solution. The enhanced guanine signal was obtained using SWCNT‐PGEs compared to one obtained by unmodified PGEs. The selectivity of genomagnetic assay was tested under optimum conditions. The DLs were calculated as 0.88 µM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In 2015, G. Congur et al. 23 found that SWCNT‐modified PGE, which was prepared by dip and dry method, showed enhanced guanine oxidation signal compared to unmodified PGE. On the basis of this enhanced signal, they used the SWCNT/PGE for electrochemical monitoring of DNA hybridization related to p53 gene sequence.…”
Section: Nanomaterial‐modified Pge For Use In Electroanalysismentioning
confidence: 64%
See 1 more Smart Citation
“…In 2015, G. Congur et al. 23 found that SWCNT‐modified PGE, which was prepared by dip and dry method, showed enhanced guanine oxidation signal compared to unmodified PGE. On the basis of this enhanced signal, they used the SWCNT/PGE for electrochemical monitoring of DNA hybridization related to p53 gene sequence.…”
Section: Nanomaterial‐modified Pge For Use In Electroanalysismentioning
confidence: 64%
“…The costs associated with constructing nanomaterial‐modified electrodes may be lower compared with conventional macroelectrodes because only tiny amounts of the nanomaterial are needed to modify the electrode surfaces. Nanomaterials composed of various metals, such as Au 17–21, Pd 22, single‐walled carbon nanotubes (SWCNT) 23, multi‐walled carbon nanotubes (MWCNTs) 24 and their composites, have been investigated and found to improve the sensitivity, selectivity, cost effectiveness, and disposability of PGEs.…”
Section: Introductionmentioning
confidence: 99%
“…The technique uses pencil graphite electrodes as a considerably cheap, disposable and environment‐friendly tool . The PeGEs have been successfully applied in various modes of DNA sensing, using either label‐free detection (usually via electrooxidation signal of guanine, e. g. ) or employing enzyme‐linked techniques involving bioaffinity labeling . The latter techniques have utilized also other types of graphite‐based electrodes and some of them involved application of magnetic beads, using the “double‐surface” approach .…”
Section: Resultsmentioning
confidence: 99%
“…The PeGEs have been successfully applied in various modes of DNA sensing, using either label‐free detection (usually via electrooxidation signal of guanine, e. g. ) or employing enzyme‐linked techniques involving bioaffinity labeling . The latter techniques have utilized also other types of graphite‐based electrodes and some of them involved application of magnetic beads, using the “double‐surface” approach . Their applications included, for example, determination of lengths of repetitive DNA sequences , detection of point mutations , or simply monitoring of PCR amplification of specific DNA fragments .…”
Section: Resultsmentioning
confidence: 99%